How great leaders think the art of reframing - Bolman, Lee G.; Deal, Terrence E. (Jossey-Bass, A Wiley Brand, 2014)
"Reframing Leadership translates Bolman & Deal's influential four-frame model of leadership and organizations developed in their bestselling Jossey-Bass Book, Reframing Organizations: Artistry, Choice and Leadership, (over 300,000 copies sold in 4 editions, $7M in net revenue) into a thought-provoking and practical guide for leaders in business and other organizations. This book will offer leaders a template and guide for understanding four major dimensions of organizational life: structure, people, politics, and symbols (or culture) that will enable them to decode the messy world in which they live, see a broader range of options, and find more powerful and elegant strategies for leading"--